Evaluasi Sistem Akuntansi Pemasukan dan Pengeluaran Kas UMKM di Kecamatan Sedayu - Renya Anjelina; Hasim As’ari (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The research entitled 'Evaluation of the Accounting System for Cash Income and Expenditures for MSMEs in Sedayu District" was carried out on 2 MSMEs, namely Angkringan Pusat and Warung Kang Bawor. With the aim of carrying out an in-depth analysis of the cash management system, especially in recording financial reports. The research results show that the largest cash expenditure comes from purchasing goods to carry out stock, while the main income comes from product sales. Apart from that, weaknesses were also found in recording financial reports, namely the combination of personal money and business money that occurred in the 2 MSMEs. This is caused by managers' lack of knowledge regarding a good financial recording system, so this is a major obstacle, so in this research it is recommended to increase education and training for managers of the Angkringan Center and Warung Kang Bawor MSME businesses. With the hope of producing financial report records that comply with standards.